Carob tree Ceratonia siliqua L. - Battle, I.; Tous, J.; Leibniz Institute of Plant Genetics and Crop Plant Research (1997)
The carob tree has been grown since antiquity in most countries of the Mediterranean region, and has spread in recent times to parts of the world with a Mediterranean climate such as California, Arizona, Mexico, Chile, Argentina, Australia, South Africa and India. This monograph describes the genetic resources of carob and reviews various aspects of its taxonomy, botany, origin, ecology, properties, uses, diversity and breeding. In addition, a full account of the crop production areas, agronomy, limitations, market, prospects and research needs is presented. It is hoped that this work will contribute to the conservation of the diversity of the cultivated carob and its wild relatives. Three appendices are supplied giving: (1) a cultivar description; (2) a list of centres of research and gene banks; and (3) a basic descriptor list for carob. (Abstract © CAB ABSTRACTS, CAB International)